Lode's angle effect on the definition of the strength criterion of porous media. (25th July 2015) - Lemarchand, Eric; Dormieux, Luc; Kondo, Djimedo; de Borst, R.; Borja, R. I.; Darve, F.; Pijaudier‐Cabot, G.; Whittle, A. J.
Summary This paper addresses the open question of the effect of the third invariant in the definition of the strength criterion of porous media. This is here achieved in the context of a porous medium made up of a solid phase, in which strength criterion appears as an explicit function of Lode's angle. Application is provided from the Gurson hollow sphere model for which the macroscopic strength exhibits a lack of symmetry for axisymmetric macroscopic strain rate loadings. Copyright © 2015 John Wiley & Sons, Ltd.